2021
DOI: 10.3389/fphar.2021.639558
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Regulated miR150-5p to Inhibit P2X7 Receptor, EMMPRIN and MMP-9 Expression in oxLDL Induced Macrophages

Abstract: Elevated extracellular matrix metalloproteinase inducer (EMMPRIN) and matrix metalloproteinase-9 (MMP-9) in oxidized low density lipoprotein (oxLDL)-induced macrophages leads to the progression of vulnerable plaques by degradation of the extracellular matrix. Our previous report showed that berberine regulates the expression of both EMMPRIN and MMP-9. In addition, P2X7 receptor (P2X7R) upregulation plays a crucial role in the development of atherosclerosis. However, it is unclear whether berberine regulated P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…BBR significantly downregulated the expression of proinflammatory genes such as IL-1β, IL-6, MCP-1, inducible NOS, cyclooxygenase-2, and MMP-9 through AMPK activation in macrophages ( Jeong et al, 2009 ). In oxLDL-induced macrophages, BBR markedly upregulated miR150-5p level and decreased P2X7R-mediated extracellular matrix metalloproteinase inducer (EMMPRIN) and MMP-9 expression ( Lu et al, 2021 ). In LPS-stimulated macrophages (RAW264.7), BBR treatment potently suppressed the expression of inflammatory cytokines such as TNF-α, IL-6, and MCP-1 through inhibition of NF-κB signaling via sirtuin 1-dependent mechanisms ( Zhang et al, 2017 ).…”
Section: Berberine Alleviated Atherosclerosis By Affecting Cellular Targetsmentioning
confidence: 99%
“…BBR significantly downregulated the expression of proinflammatory genes such as IL-1β, IL-6, MCP-1, inducible NOS, cyclooxygenase-2, and MMP-9 through AMPK activation in macrophages ( Jeong et al, 2009 ). In oxLDL-induced macrophages, BBR markedly upregulated miR150-5p level and decreased P2X7R-mediated extracellular matrix metalloproteinase inducer (EMMPRIN) and MMP-9 expression ( Lu et al, 2021 ). In LPS-stimulated macrophages (RAW264.7), BBR treatment potently suppressed the expression of inflammatory cytokines such as TNF-α, IL-6, and MCP-1 through inhibition of NF-κB signaling via sirtuin 1-dependent mechanisms ( Zhang et al, 2017 ).…”
Section: Berberine Alleviated Atherosclerosis By Affecting Cellular Targetsmentioning
confidence: 99%
“…Previous studies have found that P2X7R expression could be regulated by intracellular Cl- levels in monocytes [ 41 ]. Increased miR150-5p subsequently inhibited P2X7R expression in oxLDL-induced macrophages [ 42 ]. P2X7R level could also be regulated by microRNA-216b in human breast cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, berberine inhibits excessive autophagy, likely contributing to reduced myocardial ischemia-reperfusion injury in cardiac myocytes ( 94 ). Moreover, in an oxidized low-density lipoprotein (oxLDL)-induced macrophage model, berberine upregulated miR-150-5p level, subsequently inhibiting P2X7 receptor-mediated EMMPRIN and MMP-9 expression by suppressing AMPK-α and MAPK signaling, and exerting anti-atherogenic effects ( 95 ). Berberine has also been reported to have neuroprotective effects on ischemic brain injury by lowering intracellular ROS level, inhibiting cellular apoptosis ( 96 ), and promoting angiogenesis via AMPK-dependent microglial polarization to a homeostatic state following tMCAO ( 97 ).…”
Section: Treatments That Target Emmprin In Brain Ischemia and Ichmentioning
confidence: 99%